Electron and hydrogen transfer in organic photochemical reactions1. (10th October 2014) - Hoffmann, Norbert; Moss, R. A.; Gudmundsdottir, A.
<x xml:space="preserve">Abstract</x> Electron and hydrogen transfers are basic steps in many chemical reactions. Photochemical or electronic excitation significantly influences the reactivity of chemical compounds and thus also these transfer processes. Furthermore, the formation of typical intermediates has a decisive impact on the outcome of the transformations. Based on these properties of photochemical processes, efficient homogeneous and heterogeneous photocatalytic transformations for application to organic synthesis have been developed. Efficient reactions without any chemical activation but induced by photochemical electron transfer can also be carried out. The photon acts as a traceless reagent. In the context of photochemical hydrogen transfer, two processes are frequently encountered. The two particles the electron and the proton are transferred either simultaneously or in two steps. In the latter case, the electron is transferred first and the proton follows. Both processes are applied to organic synthesis. Copyright © 2014 John Wiley & Sons, Ltd.